Efektywność polityki wobec Romów w Polsce jako polityki publicznej - Szewczyk, Marcin (Polityka i Społeczeństwo, 2020)
The aim of the analysis is to assess the effectiveness of Polish policy towards the Roma as a public policy. The research method used is a systemic analysis, supplemented by legal and comparative analysis of the sources. The conclusion from the study is that the ethnic public policy against the Roma can be effective. However, this requires the adoption of specific assumptions. The efficacy of public ethnic policy is not associated with the efficiency. It cannot be well judged from the point of view of cost-effectiveness and the measurability of the effects in relation to investment. In addition, the evaluation needs to take into account the category of equity and recognition of European democratic and humanistic values. Such an approach is not common in European society, and discrimination against minorities is becoming more common and intense in Poland and throughout Europe. This is a key issue that may reduce the possibility of implementing public ethnic policy.